Kajian Burnout sebagai Prediktor Kinerja Buruk dan Intensi Turnover dalam Manajemen Perhotelan. Studi Kasus di Hotel Santika Premiere ICE BSD - Hasnan, Daniel Howard; Supina, Supina (Jurnal Ilmiah Pariwisata, 2024)
In the competitive business world, the hotel industry frequently struggles to retain quality personnel in today's competitive business environment. This study investigates the impact of workload on employee turnover at the Santika Premiere ICE BSD City Hotel, where it was discovered that high workload was the source of employees’ complaints. This research is centred on the importance of examining and understanding its employees' burden. The purpose of this study is to determine the association between workload and turnover intention. The workload analysis theory was used to determine how differences in workload affect turnover intention, whereas the employee turnover theory was used to study factors impacting the possibility of people leaving an organisation. This study employed quantitative approaches with a sample technique known as saturation sampling. Data collection approaches included distributing surveys to 93 hotel staff. Data analysis is carried out using basic linear regression analysis with SPSS for Windows version 26. The results reveal a result of 0.183, or 18.3%, which may be regarded as an influence between workload and turnover intention. It means that as workload grows, so does turnover intention. As a result, this study's findings have various implications for managers to consider to prevent high turnover. Keywords: workload, turnover intention, hotel, hospitality industry, burnout